Mencari Hikmah Di Balik Tradisi: Makna Dan Tujuan Aqiqah Dalam Perspektif Al-Qur'an - Mhd. A. Haris Sikumbang; Mahfudin Arif Ridho; Aswan Lubis; Harun Al-Rasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Aqiqah, the slaughter of animals as a form of gratitude for the birth of a child, is a tradition that has long been practiced by Muslims. However, as time goes by, the meaning and purpose behind this tradition sometimes becomes blurred, even trapped in empty ritualism. This article aims to explore the meaning and purpose of aqiqah based on the perspective of the Qur'an. Using a literature review method with a focus on verses and interpretations related to aqiqah, this research concludes that aqiqah is more than just a tradition. Aqiqah is a form of devotion to Allah SWT, a form of gratitude for the blessing of the birth of a child, and a prayer for the child's safety and blessings in this world and the afterlife. Through slaughtering animals, aqiqah also contains social and human values, such as sharing with the community and building relationships. This article invites readers to reflect again on the practice of aqiqah, not only as a formality, but as a means of getting closer to Allah SWT and carrying out Islamic teachings with wisdom. In this way, aqiqah can be a moment full of meaning and bring blessings to children and families.